Swordcrossed - Marske, Freya (Bramble, Tor Publishing Group, 2024)
"High heat. Low stakes. Sharp steel. The cozy, low stakes of Legends & Lattes meets the scorching bodyguard fantasy of Jennifer L. Armentrout's From Blood and Ash in this enemies-to-lovers romance where, yes, the swords do cross. Mattinesh Jay, dutiful heir to his struggling family business, needs to hire an experienced swordsman to serve as best man for his arranged marriage. Sword-challenge at the ceremony could destroy all hope of restoring his family's wealth, something that Matti has been trying -- and failing -- to do for the past ten years. What he can afford, unfortunately, is part-time con artist and full-time charming menace Luca Piere. Luca, for his part, is trying to reinvent himself in a new city. All he wants to do is make some easy money and try to forget the crime he committed in his hometown. He didn't plan on being blackmailed into giving sword lessons to a chronically responsible -- and inconveniently handsome -- wool merchant like Matti. However, neither Matti's business troubles nor Luca himself are quite what they seem. As the days count down to Matti's wedding, the two of them become entangled in the intrigue and sabotage that have brought Matti's house to the brink of ruin. And when Luca's secrets threaten to drive a blade through their growing alliance, both Matti and Luca will have to answer the question: how many lies are you prepared to strip away, when the truth could mean losing everything you want?"--